2008
DOI: 10.1111/j.1541-0072.2008.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

A Portrait of Hunger, the Social Safety Net, and the Working Poor

Abstract: In a study at the largest northeastern Iowa food pantry between 2004 and 2006, we found that neither working nor accessing government benefits has a meaningful impact on lessening the odds that a person will need long‐term food assistance. In other words, the working poor are at greater risk for making recurrent visits to the food pantry than those who do not work. Pantry clients who work are more likely to have sacrificed food to pay for other life necessities. Moreover, government benefits do not seem to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 14 publications
(21 reference statements)
2
42
0
Order By: Relevance
“…This finding affirms previous research revealing that income poverty measures underestimate the hardship condition of some working poor households (Berner, Ozer, & Paynter, 2008;Beverly, 2001a;Bradshaw & Finch, 2003;Kim et al, 2015). Working adults with low but above-poverty-level earnings have been ineligible for welfare benefits such as cash, medical, educational, and housing benefits because Korean social security system restricts its recipients to families in deep poverty and cannot cover the poor population in general (J.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding affirms previous research revealing that income poverty measures underestimate the hardship condition of some working poor households (Berner, Ozer, & Paynter, 2008;Beverly, 2001a;Bradshaw & Finch, 2003;Kim et al, 2015). Working adults with low but above-poverty-level earnings have been ineligible for welfare benefits such as cash, medical, educational, and housing benefits because Korean social security system restricts its recipients to families in deep poverty and cannot cover the poor population in general (J.…”
Section: Discussionsupporting
confidence: 79%
“…By testing the association between a household's hardship conditions and income poverty status, studies found that material hardship was more prevalent than the income poverty, and the income poor did not necessarily overlap with those who suffer from a lack of basic necessities (Berner, Ozer, & Paynter, 2008;Beverly, 2001a;Bradshaw & Finch, 2003;Chou & Lee, 2017;Dhongde & Haveman, 2016;Iceland & Bauman, 2007; S. R. Lee, 2011;Mayer & Jencks, 1989;Short, 2005). Accordingly, they suggest that hardship may be caused by other economic factors besides income such as home ownership, access to credit, income of previous year besides the current income, and in-kind welfare benefits (Beverly, 2001a;Bradshaw & Finch, 2003;Mayer & Jencks, 1989;Short, 2005).…”
Section: Materials Hardship and Income Povertymentioning
confidence: 99%
“…Dhongde and Haveman () found that almost 30% of the individuals in their study with incomes slightly above the poverty threshold experienced adverse life conditions related to health, education, and social relations. Berner et al () and Beverly () also reported that working householders were sometimes more vulnerable to material hardship than non‐working householders, even when the working ones had higher incomes.…”
Section: Introductionmentioning
confidence: 99%
“…To reveal what causes material hardship, previous research has tested the association between a household’s hardship conditions and income poverty status. These studies have shown that income poverty does not necessarily overlap with those who suffer from material hardship (Berner, Ozer, & Paynter, ; Beverly, ; Bradshaw & Finch, ; Chou & Lee, ; Dhongde & Haveman, ; Iceland & Bauman, ; Lee, ; Mayer & Jencks, ; Short, ). In Mayer and Jencks' () study, a family’s official income‐to‐needs ratio (annual family income divided by the family's official poverty threshold) explained only 24% of the variance in the amount of material hardship.…”
Section: Introductionmentioning
confidence: 99%
“…Nationally, North Carolina ranks 12th in terms of food-insecure children, with 27.3% of the state's children (618,200) categorized as food insecure and 19.3% of individuals overall categorized as food insecure (13,16). Although government assistance is available to some, it is not sufficient for many families, leaving them to seek out emergency food providers (2,9,23).…”
mentioning
confidence: 98%